A morphological and ultrastructural study of the paracloacal (Scent) glands of the marsupial Metachirus nudicaudatus Geoffroy, 1803 - Helder-Jose, [UNESP]; Freymuller, E. [UNESP] (Karger Publishers, 1995)
Morphological and ultrastructural features of the paracloacal glands of Metachirus nudicaudatus are described. Two pairs of glands, one on the right and the other on the left of the anal canal, are formed, each consisting of a major and a minor portion. Their wall is made up of three layers: a mucosal, a muscular and an external capsule. The inner one is a mucosa the epithelium of which contains holocrine cells characterized by lipid droplets and intermediate filaments. The surrounding vascular lamina propria contains flattened tubular apocrine glands whose epithelial cells contain abundant endoplasmic reticulum, prominent Golgi complexes and numerous secretory granules. The middle layer is formed by skeletal striated muscle and the outer (third layer) consists of dense connective tissue. Each gland originates from a single duct. Transverse sections show that each duct, except in the female major gland, is in fact formed by a duct system. One of these ducts comes from the central cavity, lined by holocrine epithelium, and the others result from the branched tubular glands of the lamina propria.
Keywords: Marsupial; Metachirus nudicaudatus; Opossum; Paracloacal gland; Scent gland; animal tissue; gland; nonhuman; opossum; priority journal; scent gland; ultrastructure; Animal; Comparative Study; Female; Male; Microscopy, Electron; Microscopy, Electron, Scanning; Opossums; Scent Glands; Sex Characteristics; Species Specificity